Chain code compression with modified interpolative coding. (July 2019) - Žalik, Borut; Žalik, Krista Rizman; Zupančič, Eva; Lukač, Niko; Žalik, Mitja; Mongus, Domen
Highlights: Interpolative coding is efficient at chain code compression. Interpolative coding is improved with Golomb coding. Proper selection of Golomb parameter yields slightly better compression. Abstract: A lossless chain code compression algorithm consisting of Burrows-Wheeler Transform, Move-To-Front Transform, and a modified interpolative coding is presented in this paper. The interpolative coding divides a strictly increasing array of integers and encodes the middle element recursively, where the required number of bits is obtained from the difference of the array's border values. In this paper, it is shown that, for some intervals, Golomb coding is more efficient than the interpolative coding. This fact was used to construct a hybrid approach that yields slightly better compression results than the state-of-the-art while compressing Three OrThogonal chain code, Freeman chain code in four and eight directions, and Vertex Chain Code.